A cognitive behavioral therapy program based on recycling to reduce Attention Deficit Hyperactivity Disorder (ADHD) among primary school students (Journal of the College of Basic Education, 2024)
The current research aims to reduce attention deficit hyperactivity disorder among primary school students, by building a cognitive-behavioral therapeutic program that includes a group of therapeutic techniques based on the theory of rational cognitive-behavioral therapy by Albert Ellis. The program consists of (12) sessions based on the principle of recycling.The research sample consisted of (12) male and female students in the primary stage who were diagnosed as suffering from attention deficit hyperactivity disorder and impulsivity. They were divided into two groups. The first group is the experimental group to which the research program was applied and included (6) male and female students. As for the second group, which is the control group whose members the program was not applied to, it consisted of (6) male and female students. After conducting statistical operations and in accordance with the research hypotheses, the results indicated:- There are statistically significant differences between the pre- and post-tests among the experimental group in reducing distraction among primary school students, in favor of the post-test.- There are statistically significant differences between the pre- and post-tests among the experimental group in reducing hyperactivity among primary school students, in favor of the post-test.After obtaining these results, a set of recommendations and proposals were developed.